2022
DOI: 10.1002/ep.13812
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characteristics of dried ivy gourd in a single slope solar dryer

Abstract: Ivy gourd with a good amount of potassium (K) and calcium (Ca) offers greater benefit to human health. Studying the drying mechanism of fresh ivy gourd is very important for subsequent processes and the quality of the product. The present study is intended to perform a mineral analysis (K and Ca), ash content and color parameter (L*, a*, b*, C*, H*, and whiteness and yellowness index) of solar‐dried ivy gourd. Drying experiments are performed in a single slope solar dryer and open sun drying. During the drying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Moreover, The direct sun drying showed greater b* and hue values than indirect solar dryer. Same result was found by Elangovan and Natarajan (2022) that the b* and Frontiers in Sustainable Food Systems 07 frontiersin.org hue values of dried ivy gourd sample with open drying was higher than natural and forced convection drying. In addition, the color difference showed highest change with direct sun drying compare with other drying methods.…”
Section: Color Change Of Bottle Gourdssupporting
confidence: 71%
“…Moreover, The direct sun drying showed greater b* and hue values than indirect solar dryer. Same result was found by Elangovan and Natarajan (2022) that the b* and Frontiers in Sustainable Food Systems 07 frontiersin.org hue values of dried ivy gourd sample with open drying was higher than natural and forced convection drying. In addition, the color difference showed highest change with direct sun drying compare with other drying methods.…”
Section: Color Change Of Bottle Gourdssupporting
confidence: 71%
“…The combined process of pretreatment and drying assures better antioxidant property, least color difference, and good preservation of products. Elangovan et al [28] study, the effects of pre-treatment of the red decca (or red banana) by in solutions with ascorbic acid, honey, sugar syrup and lemon juice. The best result was achieved when red decca was dipped in ascorbic acid and lemon juice as it has a higher impact on moisture loss.…”
Section: Pre-treatmentmentioning
confidence: 99%
“…According to the findings, ascorbic acid treated samples had the best effective moisture diffusivity and the lowest activation energy, whereas honey treated samples had higher sensory quality. While using single slope solar dryer and open sun drying for dehydration of ivy gourd, Elangovan and Natarajan 20 found that highest mineral values were obtained for samples dried inside a forced convection solar dryer. Also, forced convection solar dryer dried the ivy gourd sample in a minimal time with better color parameter values when compared to open sun‐dried samples.…”
Section: Introductionmentioning
confidence: 99%